The Effect of Diabetes Self Management Booklet Educational Media on Reducing Anxiety Levels in Diabetes Mellitus Patients in the Puskesmas Working Area South Cities - Irgina Raffsya P. Ibrahim; Ita Sulistiani Basir; Siti Hajar Salawali (Universitas Muhammadiyah Palu, 2026)
Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia due to impaired insulin work. DM not only has an impact on physical health but also psychologically, one of which is anxiety. Untreated anxiety can worsen a patient's quality of life and medication adherence. One of the interventions to overcome this is Diabetes Self-Management Education (DSME) using booklet media. This study aims to determine the effect of the use of DSME booklet educational media on reducing anxiety levels in DM patients in the working area of the South City Health Center. This quantitative research uses a pre-experimental design with a One Group Pretest–Posttest Design approach. The sample amounted to 49 respondents who were selected using accidental sampling techniques. Data analysis used the Wilcoxon test. The instrument in this study used the HARS questionnaire. The results showed that before being educated, the majority of respondents experienced moderate (47%) and severe (35%) anxiety. After being given the intervention through a booklet, anxiety levels decreased to mild (47%) and non-anxiety (18%). The results of the Wilcoxon test showed a p-value (0.000) < 0.05, which means that DSME booklet education had a significant effect on reducing anxiety of DM patients in the work area of the South City Health Center because it provided clear, structured, and practical information.